Altered β-catenin expression in oral mucosal dysplasia: a comparative study - Brunno Santos de Freitas SILVA; Caroline Alves de CASTRO; Sandra Lúcia Ventorin VON ZEIDLER; Suzana Cantanhede Orsini Machado de SOUSA; Aline Carvalho BATISTA; Fernanda Paula YAMAMOTO-SILVA (University of São Paulo, 2015)
Objective The current study aimed to investigate the β-catenin expression in oral leukoplakia (OL) with different degrees of epithelial dysplasia and normal oral mucosa.Material and Methods Formalin-fixed, paraffin-embedded tissue samples of 39 OL (mild dysplasia n=19, moderate dysplasia n=13, and severe dysplasia n=7), and 10 normal oral mucosa (control group) were submitted to immunohistochemical reactions to anti-β-catenin primary antibody. A qualitative β-catenin analysis was performed based on the percentage of positive cells. The cellular location and the epithelial layer were also considered. The Chi-square test and the Fisher's exact test were used to verify possible differences in the β-catenin expression among the OL groups. A p-value of <0.05 was considered statistically significant.Results Membranous expression of β-catenin in parabasal and basal layers was gradually lost in the higher degrees of epithelial dysplasia. In normal oral mucosa, β-catenin was detected only in the cytoplasmic membrane. However, a significant increase in cytoplasmic β-catenin could be observed between mild and moderate dysplasia (Fisher Exact test - p<0.001) and between mild and severe dysplasia (p<0.001).Conclusions The β-catenin cytoplasmic expression observed in this study may represent the initial stage of modifications in the E-cadherin-catenin complex, along with morphological cellular changes.